Disseminated Discoid Lupus Erythematosus and Hypothyroidism in a Vitiligo Vulgaris Patient: A Rare Coexistence - Sushil Paudel; Sameer Neupane (Nepal Journal of Dermatology, Venereology & Leprology)
Vitiligo vulgaris is a disease with multiple etiological factors including genetic, autoimmunity and several environmental factors. It has a huge psychological burden in the patient. Discoid lupus erythematosus (DLE) in the other hand can be quite disfiguring as well. Thyroid disease along with these chronic skin diseases if occurs in a same patient is really disappointing to him and his family. We report a case of 55years old man with such a rare coexistence in a patient.